A Combined Field–Lab Approach for Assessing Salmonella Infantis Persistence in Broiler Litter in a Stockpile and Composting Sleeve - Avidov, Ran; Varma, Vempalli Sudharsan; Saadi, Ibrahim; Khoury, Osama; Chen, Yona; Laor, Yael (Frontiers in Sustainable Food Systems, 2022)
Broiler litter (BL) is often contaminated by a variety of zoonotic pathogens. This study attempts to assess the persistence of Salmonella enterica serovar Infantis (S. Infantis) in BL based on spatial and temporal variation of physico-chemical properties in a stockpile and composting sleeve. A single trial of two pilot-scale setups, ca. 35 m3 each, included an open static pile (stockpile) and composting in a polyethylene sleeve with forced aeration. The initial water content was adjusted only for the sleeve (ca. 50% w/w) as in a common composting practice. Both systems were monitored weekly and then biweekly during two months in 47-53 sampling points each on every campaign. Measurements included temperature, water content, pH, electrical conductivity (EC), gas-phase oxygen and ammonia, and the collected data were used to construct multiple contour grid maps. A 83, 71, and 62% of the stockpile volume did not reach the commonly required minimum temperature of 55°C for three consecutive days during the first, second, and third week, respectively. Oxygen levels showed a strong gradient across the stockpile, while anaerobic conditions prevailed in the core. Variation was also recorded within the sleeve, but due to the water content adjustment and active aeration, the conditions favored more intense degradation and higher temperatures. Combining the grid maps drawn in this study with decay rate constants recently published for S. Infantis in BL under 36 combinations of temperature, water content, and pH (Avidov et al., 2021a), we assessed the spatial persistence of S. Infantis in the stockpile and the sleeve. Temperature was shown as a major factor, while water content and pH had only a small effect, in the stockpile only. Co-correlations between temperature, water content, EC, and oxygen suggest that selected physico-chemical properties may be sufficient for such assessments. Up to three weeks would be recommended to achieve 7-8 log10 reduction of Salmonella in a stockpile, while this would be fully achieved within one week in a sleeve. This approach of combining high‐resolution spatial field sampling along with decay rates of pathogens under controlled lab conditions may improve quantitative microbial risk assessments and future regulations of manure utilization.